The Gadir-Tyre Axis. - Álvarez-Martí-Aguilar, Manuel (Oxford University Press, 2019)
This chapter focuses on the connection between Tyre and its colony Gadir via the foundational figure of Melqart and his respective temples in these cities, a relationship which is well-known thanks to historiographical and literary testimonies dating to the Roman period. The chapter also draws a comparison with the case of the other main Tyrian colony of Carthage. This comparison allows us to note, among other things, that the religious and cultural axis which united Gadir with its metropoleis was not restricted to the colonial period itself (ninth–sixth centuries BCE) but, rather, continued to actively develop until at least the fourth century BCE.
http://biblioteca.cchs.csic.es/registro_buscareditoriales.php?id=681
Keywords: Civilización antigua - Mediterráneo (Región); Fenicios; Gadir; Tiro; Melqart